Immunohistochemical expression of cyclooxygenase-2 (COX-2) is not associated with tumor grade in feline meningiomas. (November 2018) - Samarani, F.; de la Fuente, C.; Parodi, A.; Mandara, M.T.; Pumarola, M.; Añor, S.
Highlights: Cyclooxygenase-2 (COX-2) expression in 15 feline meningiomas was assessed via immunohistochemistry. All meningiomas displayed positive immunostaining. The expression of COX-2 was not significantly correlated with WHO grade. COX-2 expression was significantly associated with the presence of necrosis. Abstract: Meningioma is the most common primary brain tumor in cats and occurs less frequently in the spinal cord. This study aimed to investigate cyclooxygenase-2 (COX-2) expression in feline meningiomas, and the possible association between COX-2 immunoreactivity and tumor grade using eight low-grade and seven high-grade meningiomas. All tumors ( n = 15/15) were immunoreactive to COX-2. The expression of COX-2 was not significantly correlated with tumor grade ( P = 0.22 and 0.34 for staining and intensity, respectively) but was significantly associated with necrosis ( P = 0.04 and 0.01 for staining and intensity, respectively). The findings in this study suggest that feline meningiomas express COX-2, but there were no differences in COX-2 immunoreactivity patterns between low- and high-grade meningiomas. However, the association between COX-2 expression and the presence of necrosis indicates a potential area for therapeutic intervention with selective COX-2 inhibitors.